Nanofibrous asymmetric membranes self-organized from chemically heterogeneous electrospun mats for skin tissue engineering. (21st June 2016) - Wu, Chaoxi; Chen, Tian; Xin, Yanjiao; Zhang, Zhen; Ren, Zhe; Lei, Jing; Chu, Bin; Wang, Yifei; Tang, Shunqing
Abstract: Asymmetric membranes, which mimic the structure and functions of human skin, have been extensively pursued as ideal skin tissue engineering constructs. In this study, we demonstrated that nanostructured asymmetric membranes can be prepared by the self-organization of chemically heterogeneous bilayer electrospun membranes in aqueous solutions. Structurally, the skin layer consists of hydrophobic β -glucan butyrate nanofibers and its inner layer consists of hydrophilic β -glucan acetate nanofibers. After the electrospinning process, both of the layers are in a dense state. When placed in water, the skin layer absorbs little water and still remains dense, but the fibers in the inner layer become extensively hydrated and spontaneously reorganize into a fully stretched structure, resulting in a significant volume increase and a density decrease of the inner layer. SEM imaging showed that β -glucan ester nanofibers exhibited a bead-free and uniform structure. Contact angle measurement and swelling tests showed that the inner layer was highly hydrophilic with extensive swelling, but the skin layer was highly hydrophobic with little swelling. Mechanical tests indicated that the nanofibrous asymmetric membranes had good mechanical properties in both the dry and wet states. In vitro cytocompatibility tests showed that nanofibrous asymmetric membranes could promote the adhesion and proliferation of fibroblasts and keratinocytes. A preliminary in vivo study performed on a full thickness mouse skin wound model demonstrated that the nanofibrous asymmetric membranes significantly accelerated the wound healing process by promoting re-epithelialization, tissue remodeling and collagen deposition. Taken together, our study provides a novel model for the design and fabrication of nanostructured asymmetric membranes, and our β -glucan based nanofibrous asymmetric membranes could be used as an advanced platform for skin tissue engineering.